Late diagnosis of lateral meningocele syndrome in a 55‐year‐old woman with symptoms of joint instability and chronic musculoskeletal pain. Issue 2 (5th December 2013) - Castori, Marco; Morlino, Silvia; Ritelli, Marco; Brancati, Francesco; De Bernardo, Carmelilia; Colombi, Marina; Grammatico, Paola
ABSTRACT Lateral meningocele syndrome (LMS) is a rare hereditary connective tissue disorder characterized by pan‐spinal meningoceles, specific facial dysmorphism, skeletal and soft tissue abnormalities, and hypotonia and/or muscle weakness. LMS has been observed in eleven patients with two instances of vertical transmission, and seven sporadic cases with an age at diagnosis ranging from 25 months to 33 years. We report on a further observation of LMS in a 55‐year‐old woman presenting with a long history of joint instability, chronic musculoskeletal pain, and iatrogenic bladder and anorectal dysfunction due to irreversible nerve damage after surgical excision of a meningeal cyst. Her clinical characteristics are compared with those of previously reported patients, as well as two further cases originally diagnosed with Hajdu–Cheney and Ehlers–Danlos syndromes, but displaying typical features of LMS. © 2013 Wiley Periodicals, Inc.